Effects of mechanical properties of muscle and tendon on performance in long distance runners - Kubo, K.; Tabata, T.; Ikebukuro, T.; Igarashi, K.; Yata, H.; Tsunoda, N. (European Journal of Applied Physiology, 2010)
The purpose of this study was to investigate the mechanical properties of muscle and tendon in long distance runners and their relations to running performance. Fifteen long distance runners (LDR) and 21 untrained subjects (CON) participated in this study. Muscle strength and activation level of knee extensors and plantar flexors were measured. Tendon elongation was determined using ultrasonography, while subjects performed ramp isometric knee extension and plantar flexion up to the voluntary maximum. Relative MVC (to body mass) of LDR was significantly lower than that of CON for knee extensors, but not for plantar flexors. No significant difference in the neural activation levels was found between LDR and CON for both sites. Maximal tendon elongation of LDR was significantly lower than that of CON for knee extensors, but not for plantar flexors. Furthermore, faster running time in a 5,000 m race (best official record of LDR) was associated with lower tendon stiffness for both sites. In conclusion, the tendon of long distance runners is less extensible than those of untrained subjects for knee extensors, but not for plantar flexors. For both sites, however, the lower tendon stiffness may be in favor of the running performance in long distance runners.